Interaction effects of desiccation and temperature stress resistance across Spodoptera frugiperda (Lepidoptera, Noctuidae) developmental stages - Keosentse, Onalethata; Mutamiswa, Reyard; Nyamukondiwa, Casper (Pensoft Publishers, 2022)
Insects encounter multiple overlapping physiologically challenging environmental stressors in their habitats. As such, the ability of insects to withstand these stressors singly or interactively is fundamental in population persistence. Following its invasion in Africa, Spodoptera frugiperda (Lepidoptera: Noctuidae) has successfully established and spread in most parts of the continent. However, the mechanisms behind its successful survival across arid and semi-arid African environments are relatively unknown. Here, we investigated the water balance of S. frugiperda across its developmental stages. Given the relationships between desiccation stress, temperature stress and other life history traits in arid ecosystems, we also measured interaction effects across metrics of these traits. Specifically, we measured basal body water content (BWC), water loss rates (WLRs) and the effects of desiccation pre-treatment on critical thermal minimum (CTmin), critical thermal maximum (CTmax) and fecundity. Body water content and WLR increased with age across larval instars. However, the effects of desiccation environments on WLRs were more dramatic for 5th and 6th larval instars. The 5th and 6th instars exhibited highest BWC and magnitude of WLRs plastic responses following desiccation treatment. The effects of desiccation pre-treatment on temperature tolerance were less apparent, only significantly improving CTmin in 2nd and 3rd larval instars and reducing CTmax in 5th instars. In addition, desiccation pre-treatment showed no significant effects on fecundity. These results show that water balance traits differ with developmental stage, while the effects of desiccation pre-treatment were more dramatic and inconclusive. The differential desiccation resistance, high proportional BWC and no desiccation pre-treatment effects on fecundity may help the species survive in arid and semi-arid environments. This information provides insights into understanding S. frugiperda survival under desiccating arid and semi-arid tropical environments and is significant in predicting pest outbreaks.